Exploring the Relationship Between Foot Position and Reduced Risk of Knee-Related Injuries in Side-Cutting Movements - Xiuye Qu; Datao Xu; Xiaowei Yang; Ukadike Chris Ugbolue; Huiyu Zhou; Yaodong Gu (Applied Sciences)
Background: Knee-related injuries often result from poor movement patterns that destabilize the joint and increase stress on knee structures. Understanding the influence of foot positioning on knee biomechanics is critical for identifying high-risk movement patterns and preventing injuries. Methods: Twenty healthy male participants performed side-cutting movements at three different foot progression angles. One participant’s data were used to develop and validate a knee finite element model with high-speed dual fluoroscopic imaging (DFIS). Combined with a musculoskeletal analysis, the model simulated internal knee loads under various foot-positioning conditions. Results: The analysis revealed that, as the external foot progression angle increased, the ankle plantarflexion decreased, while the ankle internal rotation and knee valgus moments increased. Higher stress concentrations were observed on the ACL, lateral meniscus, lateral tibial cartilage, and medial collateral ligament, particularly at the femoral–tibial ACL attachments. Conclusion: The findings suggest that a toe-out foot position elevates the risk of knee injuries by increasing stress on key structures, whereas a toe-in position may enhance joint stability, reduce the ACL injury risk, and promote favorable muscle activation patterns.